Serum Thyrotropin and Phase of the Menstrual Cycle - Benvenga, Salvatore; Di Bari, Flavia; Granese, Roberta; Antonelli, Alessandro (Frontiers in Endocrinology, 2017)
About 1/5 of patients treated with levothyroxine have serum thyrotropin (TSH) above target concentrations, but in approximately 15% of them the cause of this TSH insufficient normalization remains unknown. We report the cases of two regularly menstruating women with known thyroid disease who had TSH levels consistently >3 mIU/ml (and sometimes above target levels) during mid-cycle, but consistently lower serum levels during the follicular and luteal phases of menstrual cycle. A major TSH release by the thyrotrophs in response to high circulating levels of estradiol (E2) at mid-cycle may increase levels of TSH compared to other phases of the cycle. The increased TSH can be misinterpreted as refractory hypothyroidism if the woman is under L-T4 replacement therapy or as subclinical hypothyroidism if the woman is not. Our findings might have important implications for diagnosis and management of thyroid disease, suggesting to request serum TSH measurements outside of the periovulatory days.